Acupuncture to improve tolerance of diagnostic esophagogastroduodenoscopy in patients without systemic sedation: results of a single-center, double-blinded, randomized controlled trial (DRKS00000164). Issue 1 (December 2016) - Schaible, Anja; Schwan, Katja; Bruckner, Thomas; Plaschke, Konstanze; Büchler, Markus; Weigand, Markus; Sauer, Peter; Bopp, Christian; Knebel, Phillip
Abstract Background Sedation prior to esophagogastroduodenoscopy is widespread and increases patient comfort. However, it demands additional trained personnel, accounts for up to 40 % of total endoscopy costs and impedes rapid hospital discharge. Most patients lose at least one day of work. 98 % of all serious adverse events occurring during esophagogastroduodenoscopy are ascribed to sedation. Acupuncture is reported to be effective as a supportive intervention for gastrointestinal endoscopy, similar to conventional premedication. We investigated whether acupuncture during elective diagnostic esophagogastroduodenoscopy could increase the comfort of patients refusing systemic sedation. Methods We performed a single-center, double-blinded, placebo-controlled superiority trial to compare the success rates of elective diagnostic esophagogastroduodenoscopies using real and placebo acupuncture. All patients aged 18 years or older scheduled for elective, diagnostic esophagogastroduodenoscopy who refused systemic sedation were eligible; 354 patients were randomized. The primary endpoint measure was the rate of successful esophagogastroduodenoscopies. The intervention was real or placebo acupuncture before and during esophagogastroduodenoscopy. Successful esophagogastroduodenoscopy was based on a composite score of patient satisfaction with the procedure on a Likert scale as well as quality of examination, as assessed by the examiner. Results From February 2010 to July 2012, 678 patients were screened; 354 were included in the study. Baseline characteristics of the two groups showed a similar distribution in all but one parameter: more current smokers were allocated to the placebo group. The intention-to-treat analysis included 177 randomized patients in each group. Endoscopy could successfully be performed in 130 patients (73.5 %) in the real acupuncture group and 129 patients (72.9 %) in the placebo group. Willingness to repeat the procedure under the same conditions was 86.9 % in the real acupuncture group and 87.6 % in the placebo acupuncture group. Conclusions Esophagogastroduodenoscopy without sedation is safe and can successfully be performed in two-thirds of patients. Patients planned for elective esophagogastroduodenoscopy without sedation do not benefit from acupuncture of the Sinarteria respondens (Rs) 24 Chengjiang middle line, Pericard (Pc) 6 Neiguan bilateral, or Dickdarm (IC) 4 Hegu bilateral, according to traditional Chinese medicine meridian theory. Trial registration DRKS00000164 . Registered on 10 December 2009.